Acute osimertinib exposure induces electrocardiac changes by synchronously inhibiting the currents of cardiac ion channels - Li, Peiwen; Tian, Xiaohui; Wang, Gongxin; Jiang, Enshe; Li, Yanming; Hao, Guoliang (Frontiers in Pharmacology, 2023)
Introduction: As the third generation of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), osimertinib has demonstrated more significant cardiotoxicity than previous generations of EGFR-TKIs. Investigating the mechanism of osimertinib cardiotoxicity can provide a reference for a comprehensive understanding of osimertinib-induced cardiotoxicity and the safety of the usage of this drug in clinical practice. Methods: Multichannel electrical mapping with synchronous ECG recording was used to investigate the effects of varying osimertinib concentrations on electrophysiological indicators in isolated Langendorff-perfused hearts of guinea pigs. Additionally, a whole-cell patch clamp was used to detect the impact of osimertinib on the currents of hERG channels transfected into HEK293 cells and the Nav1.5 channel transfected into Chinese hamster ovary cells and acute isolated ventricular myocytes from SD rats. Results: Acute exposure to varying osimertinib concentrations produced prolongation in the PR interval, QT interval, and QRS complex in isolated hearts of guinea pigs. Meanwhile, this exposure could concentration-dependently increase the conduction time in the left atrium, left ventricle, and atrioventricular without affecting the left ventricle conduction velocity. Osimertinib inhibited the hERG channel in a concentration-dependent manner, with an IC50 of 2.21 ± 1.29 μM. Osimertinib also inhibited the Nav1.5 channel in a concentration-dependent manner, with IC50 values in the absence of inactivation, 20% inactivation, and 50% inactivation of 15.58 ± 0.83 μM, 3.24 ± 0.09 μM, and 2.03 ± 0.57 μM, respectively. Osimertinib slightly inhibited the currents of L-type Ca2+ channels in a concentration-dependent manner in acutely isolated rat ventricular myocytes. Discussion: Osimertinib could prolong the QT interval; PR interval; QRS complex; left atrium, left ventricle, and atrioventricular conduction time in isolated guinea pig hearts. Furthermore, osimertinib could block the hERG, Nav1.5, and L-type Ca2+ channels in concentration-dependent manners. Therefore, these findings might be the leading cause of the cardiotoxicity effects, such as QT prolongation and decreased left ventricular ejection fraction.